Studien zur Volkskunde Südosteuropas und des mediterranen Raums - Puchner, Walter (2009)
This volume includes 24 studies on comparative culture analysis in the Southeastern-European and Mediterrean area, as practizised in the "Ethnologia europaea" of Leopold Kretzenbacher, giving an idea of the plurality of possible topics and issues of folk culture in history and presence of this oldest part of Europe, which has not yet been really explored by interested readers. In t erms of subjects and methods these studies are partly located beyond the traditional thematical set of folklore studies: theoretical and terminological problems are discussed, cultural history since the late antiquity is involved, theological issues come together with research facts on customs and rites, masques and disguisings, issues of gender studies and sociology af ages are brought together with methodological critics on comparativism of the Victorian school of ethnography, the competitions of tournament are analyzed in historical and functional context as symbols of power and superiority of Venice in the Eastern Mediterrean, folk plays are examined as prefigurating structures of elaborated forms of folk theatre as well as the influences of Byzantine ecclesiastic painting and iconography on orthodox folk culture; other chapters focus on ethnosteretyps, on forms and functions of blood brotherhood (adoptio in fratrem) since late antiquity, the ways of reception of popular reading material throughout the Balkan peninsula since the 16th century are presented. Other studies are dedicated to the formation of religious traditions in West and East, between Catholicism and Orthodoxy, to fairy tales between orality and literacy, but also topics like the public display of personal feelings, forms of gestures, figures of demonology, narratives of oral autobiography, etymological and semantic questions are examined and research projects on oral folk literature are presented. One chapter is also dedicated to the ideological use of folklore studies in the nineteenth century. Chapters 15-24 focus more sepcifically on Greece without lacking wider comparative views. The Introduction and the Conclusion, the selected bibliography at the end of the volume and the indices integrate these chapters in a unique perspective. The specific indices allow also a selective use of the volume.